Increased intra-abdominal pressure affects respiratory variations in arterial pressure in normovolaemic and hypovolaemic mechanically ventilated healthy pigs - Duperret, Serge; Lhuillier, Franck; Piriou, Vincent; Vivier, Emmanuel; Metton, Olivier; Branche, Patricia; Annat, Guy; Bendjelid, Karim; Viale, Jean Paul (Intensive care medicine, 2007)
To evaluate the effect of increased intra-abdominal pressure (IAP) on the systolic and pulse pressure variations induced by positive pressure ventilation in a porcine model. Experimental study in a research laboratory. Seven mechanically ventilated and instrumented pigs prone to normovolaemia and hypovolaemia by blood withdrawal. Abdominal banding gradually increased IAP in 5-mmHg steps up to 30 mmHg. Variations in systolic pressure, pulse pressure, inferior vena cava flow, and pleural and transmural (LVEDPtm) left-ventricular end-diastolic pressure were recorded at each step. Systolic pressure variations were 6.1+/-3.1%, 8.5+/-3.6% and 16.0+/-5.0% at 0, 10, and 30 mmHg IAP in normovolaemic animals (mean+/-SD; p<0.01 for IAP effect). They were 12.7+/-4.6%, 13.4+/-6.7%, and 23.4+/-6.3% in hypovolaemic animals (p<0.01 vs normovolaemic group) for the same IAP. Fluctuations of the inferior vena cava flow disappeared as the IAP increased. Breath cycle did not induce any variations of LVEDPtm for 0 and 30 mmHg IAP. In this model, the systolic pressure and pulse pressure variations, and inferior vena cava flow fluctuations were dependent on IAP values which caused changes in pleural pressure swing, and this dependency was more marked during hypovolaemia. The present study suggests that dynamic indices are not exclusively related to volaemia in the presence of increased IAP. However, their fluid responsiveness predictive value could not be ascertained as no fluid challenge was performed.